2019
DOI: 10.1101/525303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A role for ATP Citrate Lyase in cell cycle regulation during myeloid differentiation

Abstract: 1Differentiation of myeloid progenitor cells into macrophages is accompanied by increased 2 PU.1 concentration and increasing cell cycle length, culminating in cell cycle arrest. Induction of 3 PU.1 expression in a cultured myeloid cell line expressing low PU.1 concentration results in 4 decreased levels of mRNA encoding ATP-Citrate Lyase (ACL) and cell cycle arrest. ACL is an 5 essential enzyme for generating acetyl-CoA, a key metabolite for the first step in fatty acid 6 synthesis as well as for histone acet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…FACS/immunoblot analyses revealed the presence of novel forms of G-3-pHis+ ACLY protein in TAMs (Fig 4). Although the role of ACLY in myeloid cells has been explored in the literature (Covarrubias et al, 2016; de Goede et al, 2021; Lauterbach et al, 2019; Namgaladze et al, 2018; Rhee et al, 2019; Verberk et al, 2021), the expression of non-canonical ACLY isoforms in CD11b+Ly6G-myeloid cells has not been previously described and the origin and function of these isoforms is the subject of ongoing research.…”
Section: Discussionmentioning
confidence: 99%
“…FACS/immunoblot analyses revealed the presence of novel forms of G-3-pHis+ ACLY protein in TAMs (Fig 4). Although the role of ACLY in myeloid cells has been explored in the literature (Covarrubias et al, 2016; de Goede et al, 2021; Lauterbach et al, 2019; Namgaladze et al, 2018; Rhee et al, 2019; Verberk et al, 2021), the expression of non-canonical ACLY isoforms in CD11b+Ly6G-myeloid cells has not been previously described and the origin and function of these isoforms is the subject of ongoing research.…”
Section: Discussionmentioning
confidence: 99%
“…We selected Tp53 as a gene that is expected to be upregulated in unstimulated B cells because of its well-documented increase in expression during apoptosis (30). Acly was chosen as a gene expected to be downregulated because of its role in fatty acid synthesis during cell division (31). We found that Tp53 was upregulated over time by 12-fold in unstimulated B cells (Fig.…”
Section: Spic Expression Is Increased By Quiescence In Primary Spleni...mentioning
confidence: 97%
“…The cell cycle is an irreversible process, and its progression is orchestrated through sequential activation of cyclin‐dependent kinases (CDKs) by their proper cyclin partner . In addition, CDK1/2/4/6 plays essential roles in cell cycle progression, which are highly disturbed in cancer cells . CDK4/6 mainly controls cell growth in G1 phase, CDK2 regulates chromosomal replication, and CDK1 regulates mitosis and meiosis .…”
Section: Introductionmentioning
confidence: 99%
“…[4] In addition, CDK1/2/4/6 plays essential roles in cell cycle progression, which are highly disturbed in cancer cells. [5,6] CDK4/6 mainly controls cell growth in G1 phase, CDK2 regulates chromosomal replication, and CDK1 regulates mitosis and meiosis. [4,5] Therefore, tumour cell growth is inhibited by arrest of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%